2000
DOI: 10.1088/0953-8984/12/8a/302
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of liquid transition metals studied by time resolved photoelectron spectroscopy

Abstract: The electronic structure of liquid transition metals has been studied by time resolved photoelectron spectroscopy. Distinct changes in the valence band structure across the solid-liquid phase transitions have been observed for Pd, Mo and W. In the case of Pd the changes on melting are caused by a change in the photoemission process itself. For Nb, Mo, Ta and W we suggest a change in the atomic short range order from the bcc structure to an fcc-like short range order in the liquid state which causes a marked ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…The 4d−band envelop is significantly affected when the temperature increases. The structures disappear to form a fairly flat and slightly broadened band, as illustrated in the calculation performed at 20,000 K. Such behavior is observed at temperatures as low as 4,000 K confirming that it is highly correlated with the transition from solid to liquid phase, as previously reported in photoelectron spectroscopy measurements 34,35 . The decrease in density results in a negative energy shift of both the 4d−band and the Fermi energy E F .…”
supporting
confidence: 86%
“…The 4d−band envelop is significantly affected when the temperature increases. The structures disappear to form a fairly flat and slightly broadened band, as illustrated in the calculation performed at 20,000 K. Such behavior is observed at temperatures as low as 4,000 K confirming that it is highly correlated with the transition from solid to liquid phase, as previously reported in photoelectron spectroscopy measurements 34,35 . The decrease in density results in a negative energy shift of both the 4d−band and the Fermi energy E F .…”
supporting
confidence: 86%
“…show changes in the DOS in the solid and liquid which reflect the changes in atomic ordering from bcc to a close-packed-like ordering [23][24][25].…”
Section: Molybdenummentioning
confidence: 99%
“…On the basis of extensive experimental [1][2][3][4][5][6][7][8][9][10][11] and theoretical studies of the phase diagram of Mo the following can be safely concluded. The body-centered cubic (bcc) phase of Mo is extremely stable up to very high pressures, at least in excess of 5 Mbars.…”
mentioning
confidence: 99%